Test Variability of the QuantiFERON-TB Gold In-Tube Assay in Clinical Practice - Metcalfe, John Z.; Cattamanchi, Adithya; McCulloch, Charles E.; Lew, Justin D.; Ha, Ngan P.; Graviss, Edward A. (American journal of respiratory and critical care medicine, 2013)
Although IFN-γ release assays (IGRAs) are widely used to screen for Mycobacterium tuberculosis infection in high-income countries, published data on repeatability are limited. To determine IGRA repeatability. The study population included consecutive patients referred to The Methodist Hospital (Houston, TX) between August 1, 2010 and July 31, 2011 for latent tuberculosis (TB) infection screening with an IGRA (QuantiFERON-TB Gold In-Tube; Cellestis, Carnegie, Australia). We performed multiple IGRA tests using leftover stimulated plasma according to a prospectively formulated quality control protocol. We analyzed agreement in interpretation of test results classified according to manufacturer-recommended criteria and repeatability of quantitative TB response. During the study period, 1,086 test results were obtained from 543 subjects. Per the manufacturer's cut-point, the result of the second test was discordant from that of the first in 28 (8%) of 366 patients with valid test results, including 13 with an initial negative result and 15 with an initial positive result. Although agreement between repeat test results was high (κ = 0.84; 95% confidence interval, 0.79-0.90), the normal expected range of within-subject variability in TB response on retesting included differences of ± 0.60 IU/ml for all individuals (coefficient of variation, 14%), and ± 0.24 IU/ml (coefficient of variation, 27%) for individuals whose initial TB response was between 0.25 and 0.80 IU/ml. There is substantial variability in TB response when IGRAs are repeated using the same patient sample. IGRA results should be interpreted cautiously when TB response is near interpretation cut-points.